1979
DOI: 10.3109/00016487909126399
|View full text |Cite
|
Sign up to set email alerts
|

Function of Submaxillary Gland Following Iatrogenic Damage to Chorda Tympani Nerve

Abstract: Flow rate, protein and amylase content of submaxillary saliva were determined before and after iatrogenic damage to the chorda tympani nerve during otosurgery. Parallel to these investigations, gustatory function was checked. Chronic otopathy itself did not lead to a disturbance of either the sense of taste or the function of the submaxillary gland in any of the 14 patients. On the other hand, the flow rate of the affected gland dropped after chorda division (8 patients) and after chorda stretching (6 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
(7 reference statements)
0
10
0
Order By: Relevance
“…In cases involving CT trauma sustained during otologic surgery, advances in technique have eased the recovery process: Oral sequelae are less frequent when the CT is stretched rather than cut [31-37] and recovery rates following transection are highest when the cut ends are reattached [38, 39]. Still, in these and other cases of CT damage, follow-up taste testing often reveals persistent change and incomplete recovery of function [e.g., 36, 40, 41].…”
Section: Consequences Of Oral Sensory Nerve Damagementioning
confidence: 99%
“…In cases involving CT trauma sustained during otologic surgery, advances in technique have eased the recovery process: Oral sequelae are less frequent when the CT is stretched rather than cut [31-37] and recovery rates following transection are highest when the cut ends are reattached [38, 39]. Still, in these and other cases of CT damage, follow-up taste testing often reveals persistent change and incomplete recovery of function [e.g., 36, 40, 41].…”
Section: Consequences Of Oral Sensory Nerve Damagementioning
confidence: 99%
“…Some patients are asymptomatic, whilst others can have transient or permanent symptoms 1 3 . Numerous factors influence which of these three outcomes occurs, the most important being whether the chorda tympani has been sectioned or is grossly intact 2 , 3 , 10 , 19 , 22 , 28 30 . Others include the type of surgery, 2 , 31 the age of the patient, 30 , 32 whether the injury is unilateral or bilateral, 7 , 33 and the underlying disease 1 , 2 , 9 , 32 , 34 …”
Section: What Are the Effects Of Chorda Tympani Injury?mentioning
confidence: 99%
“…Chilla et al 28 found that ipsilateral submandibular gland salivary flow was significantly decreased after chorda tympani injury, but not enough to cause symptoms. When the patients were retested four years later, submandibular salivary flow remained diminished, but only in those whose chorda tympani had been divided 29 …”
Section: What Are the Effects Of Chorda Tympani Injury?mentioning
confidence: 99%
“…The levels of phosphorus and potassium at the operated side were found to be significantly lower compared to those at the healthy side. In the study of Chilla et al [8], the changes in the rate of saliva secretion, and in the concentrations of amylase and protein in saliva were investigated in two groups of patients; the chorda tympani nerve cut group and the chorda tympani excessively stretched group. As in the other studies, the rate of saliva secretion decreased, but not ceased.…”
Section: Discussionmentioning
confidence: 99%